1988
DOI: 10.1007/bf00276148
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme kinetics for a two-step enzymic reaction with comparable initial enzyme-substrate ratios

Abstract: We extend the validity of the quasi-steady state assumption for a model double intermediate enzyme-substrate reaction to include the case where the ratio of initial enzyme to substrate concentration is not necessarily small. Simple analytical solutions are obtained when the reaction rates and the initial substrate concentration satisfy a certain condition. These analytical solutions compare favourably with numerical solutions of the full system of differential equations describing the reaction. Experimental me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…In the case of the system here, we discussed this hypothesis in Levine et al (2000Levine et al ( , 2001. Other sources include Frenzen and Maini (1988), Segel (1988) and Segel and Slemrod (1989).…”
Section: The Equations Of Mass Actionmentioning
confidence: 99%
“…In the case of the system here, we discussed this hypothesis in Levine et al (2000Levine et al ( , 2001. Other sources include Frenzen and Maini (1988), Segel (1988) and Segel and Slemrod (1989).…”
Section: The Equations Of Mass Actionmentioning
confidence: 99%
“…To obtain the reduced model corresponding to ZDP 1 , we substitute from Eqn (20) into the first ODE in Eqn (11) …”
Section: Accurate Enzyme Kinetics Based On Zdpmentioning
confidence: 99%
“…Using the tabulated ZDP 1 manifold to reduce the PTS model As we show above, an explicit expression for a ZDP manifold, such as Eqn (20), can be used to obtain a lower-dimensional model, such as Eqn (21). When a ZDP manifold is only available in tabulated form, however, such a reduced equation cannot be written out explicitly.…”
Section: Calculation Of Zdp Manifolds For the Pts Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence for this is not conclusive. Segel (1988);Segel and Slemrod (1989) and Frenzen and Maini (1988) have shown that the sQSSA can provide a good approximation even when ½S 0 % ½E 0 as long as [E 0 ] is small compared to K M . The positive [S 0 ]-[E 0 ] plane can be divided into regions in which these approximations hold, but in certain circumstances there remains a region where neither holds.…”
Section: Validity Of the Quasi-steady-state Approximationmentioning
confidence: 99%